2013
DOI: 10.1021/ja404181c
|View full text |Cite
|
Sign up to set email alerts
|

Monocopper Doping in Cd-In-S Supertetrahedral Nanocluster via Two-Step Strategy and Enhanced Photoelectric Response

Abstract: We apply a two-step strategy to realize ordered distribution of multiple components in one nanocluster (NC) with a crystallographically ordered core/shell structure. A coreless supertetrahedral chalcogenide Cd-In-S cluster is prepared, and then a copper ion is inserted at its void core site through a diffusion process to form a Cu-Cd-In-S quaternary NC. This intriguing molecular cluster with mono-copper core and Cd-In shell exhibits enhanced visible-light-responsive optical and photoelectric properties compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 30 publications
2
82
0
Order By: Relevance
“…6b), which indicates that the SD/Ag88b possesses the best efficiency in the generation and separation of photoinduced electron/hole pairs in ITO electrodes. 47 The photocurrent density can be still ARTICLE kept after ten on/off cycles, suggesting the response reproducibility. The generation of photocurrent may involve photoinduced charge migration from S 3p to the Ag 5 s orbits.…”
Section: Resultsmentioning
confidence: 91%
“…6b), which indicates that the SD/Ag88b possesses the best efficiency in the generation and separation of photoinduced electron/hole pairs in ITO electrodes. 47 The photocurrent density can be still ARTICLE kept after ten on/off cycles, suggesting the response reproducibility. The generation of photocurrent may involve photoinduced charge migration from S 3p to the Ag 5 s orbits.…”
Section: Resultsmentioning
confidence: 91%
“…Considerable attention has been paid and substantial successes have been achieved in inorganic-organic hybrid main-group metal chalcogenidometalates. It has been revealed that the integration of organic components with inorganic chalcogenide structures can produce materials with well-defined various topological structures and hold promise for applications in ion exchange, nonlinear optics, electronics and catalysis [1][2][3][4][5][6]. According to the classification of cation components, the inorganic-organic hybrid main-group metalchalcogenidometalates can be generally divided into third categories.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Hydrogen, which is the simplest form of energy transporter,can be generated renewablyf rom solar energy through water splitting. [4][5][6][7][8][9][10][11] Recently,s emiconducting oxide photoanodes have been coated with a(compact) layer of oxygen evolutione lectrocatalyst. PEC devices are most advantageous for water splitting ast hey incorporateb oth solar-energy collection and water electrolysis in as ingle reactor.H owever, water splitting with solarr adiation has been ac hallengingt ask for the scientific community for the last four decades.…”
Section: Introductionmentioning
confidence: 99%
“…Al ot of effort has been devoted to the design and fabrication of new nanostructures with various types of metal oxide semiconductors such as TiO 2 ,N aNbO 3 , SrTiO 3 ,B aTiO 3 , a-Fe 2 O 3 ,a nd WO 3 as well as non-oxide semiconductorss uch as CdS, CdSe, Ag 2 S, GaAs, InP,C uInS 2 ,a nd CdTe to improvet he energy-conversion efficiency. [4][5][6][7][8][9][10][11] Recently,s emiconducting oxide photoanodes have been coated with a(compact) layer of oxygen evolutione lectrocatalyst. [12][13][14] However,i na ddition to the decreased incident-light absorption, am ajor limitation of this concept lies in the difficulty to depositt he electrocatalyst layer inside an anoporous semiconductor network.…”
Section: Introductionmentioning
confidence: 99%